Palliative Surgery for Malignant Bowel Obstruction from Carcinomatosis: A Systematic Review - Paul Olson, Terrah J. (2014)
IMPORTANCE: Care of patients with malignant bowel obstruction caused by peritoneal metastases may present an ethical dilemma for surgeons when nonoperative management fails. OBJECTIVE: To characterize outcomes of palliative surgery for malignant bowel obstruction from peritoneal carcinomatosis to guide decision making about surgery and postoperative interventions for patients with terminal illness. EVIDENCE REVIEW: We searched PubMed, EMBASE, Cochrane Library, Web of Knowledge, CINAHL Plus, and Google Scholar, and performed manual searches of selected journals from inception to August 30, 2012 with no filters, limits, or language restrictions. We used database-specific combinations of intestinal obstruction, malignant, surgery or surgical, and palliat*. We included studies reporting outcomes after palliative surgery for malignant bowel obstruction from peritoneal carcinomatosis from any primary malignancy and excluded case studies, curative surgery, isolated percutaneous procedures, stenting for intraluminal lesions, and studies in which benign and malignant obstructions could not be distinguished. We assessed quality with the Newcastle-Ottawa Scale. FINDINGS: We screened 2347 unique articles, selected 108 articles for full-text review, and included 17 studies. Surgery was able to palliate obstructive symptoms for 32 to 100% of patients, enable resumption of a diet for 45 to 75% of patients, and facilitate discharge to home in 34–87% of patients. Mortality was high (6–32%), and serious complications are common (7–44%). Frequent re-obstructions (6–47%), readmissions (38–74%), and re-operations (2–15%) occur. Survival was limited (median 26–237 days), and hospitalization for surgery consumed a substantial portion of the patient’s remaining life (11–61%). CONCLUSIONS AND RELEVANCE: Although palliative surgery can benefit patients, it comes at the cost of high mortality and substantial hospitalization relative to the patient’s remaining survival time. Preoperatively, surgeons should present realistic goals and limitations of surgery. For patients choosing surgery, clarifying preferences for aggressive postoperative interventions preoperatively is critical given the high complication rate and limited survival after surgery for malignant bowel obstruction.